Cerebellar Transcranial Magnetic Stimulation Reduces the Silent Period on Hand Muscle Electromyography During Force Control - Akiyoshi Matsugi; Shinya Douchi; Kodai Suzuki; Kosuke Oku; Nobuhiko Mori; Hiroaki Tanaka; Satoru Nishishita; Kyota Bando; Yutaka Kikuchi; Yohei Okada (Brain Sciences, 2020)
This study aimed to investigate whether cerebellar transcranial magnetic stimulation (C-TMS) affected the cortical silent period (cSP) induced by TMS over the primary motor cortex (M1) and the effect of interstimulus interval (ISI) on cerebellar conditioning and TMS to the left M1 (M1-TMS). Fourteen healthy adult participants were instructed to control the abduction force of the right index finger to 20% of the maximum voluntary contraction. M1-TMS was delivered during this to induce cSP on electromyograph of the right first dorsal interosseous muscle. TMS over the right cerebellum (C-TMS) was conducted prior to M1-TMS. In the first experiment, M1-TMS intensity was set to 1 or 1.3 × resting motor threshold (rMT) with 20-ms ISI. In the second experiment, the intensity was set to 1 × rMT with ISI of 0, 10, 20, 30, 40, 50, 60, 70, or 80 ms, and no-C-TMS trials were inserted. In results, cSP was significantly shorter in 1 × rMT condition than in 1.3 × rMT by C-TMS, and cSP was significantly shorter for ISI of 20−40 ms than for the no-C-TMS condition. Further, motor evoked potential for ISI40-60 ms were significantly reduced than that for ISI0. Thus, C-TMS may reduce cSP induced by M1-TMS with ISI of 20−40 ms.